Fluid-Attenuated Inversion Recovery May Serve As a Tissue Clock in Patients Treated With Endovascular Thrombectomy. Issue 7 (7th May 2021) - Aoki, Junya; Sakamoto, Yuki; Suzuki, Kentaro; Nishi, Yuji; Kutsuna, Akihito; Takei, Yukako; Sawada, Kazutaka; Kanamaru, Takuya; Abe, Arata; Katano, Takehiro; Takeshi, Yuho; Nakagami, Toru; et al.
Abstract : Background and Purpose: We investigated whether the signal change on fluid-attenuated inversion recovery (FLAIR) can serve as a tissue clock that predicts the clinical outcome after endovascular thrombectomy (EVT), independently of the onset-to-admission time. Methods: Consecutive patients with acute stroke treated with EVT between September 2014 and December 2018 were enrolled. Based on the parenchymal signal change on FLAIR, patients were classified into FLAIR-negative and FLAIR-positive groups. The clinical characteristics, imaging findings, EVT parameters, and the intracranial hemorrhage defined as Heidelberg Bleeding Classification ≥1c hemorrhage (parenchymal hemorrhage, intraventricular hemorrhage, subarachnoid hemorrhage, and/or subdural hemorrhage) were compared between the 2 groups. A modified Rankin Scale score 0 to 1 at 3 months was considered to represent a good outcome. Results: Of the 227 patients with EVT during the study period, 140 patients (62%) were classified into the FLAIR-negative group and 87 (38%) were classified into the FLAIR-positive group. In the FLAIR-negative group, the patients were older ( P =0.011), the onset-to-image time was shorter ( P <0.001), the frequency of cardioembolic stroke was higher ( P =0.006), and the rate of intravenous thrombolysis was higher ( P <0.001) in comparison to the FLAIR-positive group. Although the rate of complete recanalization after EVT did not differ between the 2 groups ( P =0.173), the frequency of both any-intracranial hemorrhage and Heidelberg Bleeding Classification ≥1c hemorrhage were higher in the FLAIR-positive group ( P =0.004 and 0.011). At 3 months, the percentage of patients with a good outcome (FLAIR-negative, 41%; FLAIR-positive, 27%) was significantly related to the FLAIR signal change ( P =0.047), while the onset-to-image time was not significant ( P =0.271). A multivariate regression analysis showed that a FLAIR-negative status was independently associated with a good outcome (odds ratio, 2.10 [95% CI, 1.02–4.31], P =0.044). Conclusions: A FLAIR-negative status may predict the clinical outcome more accurately than the onset-to-admission time, which may support the role of FLAIR as a tissue clock.